The Effect of Service Quality, Perceived Usefulness of Mobile Banking, and Customer Trust during Pandemic Covid-19 on Customer Loyalty through Customer Satisfaction in the Banking Sector - Devi Ayu Rahmatika; Harry Soesanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Covid-19 pandemic is not only a global health problem but also has an impact on various sectors of the global economy, including the banking sector. One of the impacts of Covid-19 on the banking sector is a significant decrease in the number of customers. The decline was experienced by Bank BRI Unit Kota Tegal. The problem that occurs in this research is how to increase customer satisfaction and loyalty which will maintain the number of customers and have an impact on increasing the number of customers of Bank BRI Unit Kota Tegal. The variable data used in this study were obtained from two hundred and twenty customers of Bank BRI Unit Kota Tegal who were given questionnaire data containing questions. The data is then forwarded to be processed using the SEM analysis technique and then forwarded using the AMOS analysis tool. The results showed that the influence of the service quality variable on the customer satisfaction variable was 4,368 where this value was greater than 1.96 and also the p value was much smaller than 0.05, and the customer trust variable on the customer satisfaction variable was 3,218 where this value was greater. of 1.96 and also the p-value of 0.001 which is smaller than 0.05, the customer loyalty variable of 3.827 where this value is greater than 1.96, and also the p value is much smaller than 0.05. This means that service quality, customer trust, and customer satisfaction are factors that can maintain and influence the increase in the number of customers of Bank Rakyat Indonesia Tegal City Unit.